Oropharyngeal dysphagia in people with head and neck cancer: a case study - Ambiado-Lillo, Manuel Matías (Revista de Investigación en Logopedia, 2024)
Head and Neck Cancer is one of the most common malignant conditions in the world, with high mortality rates. Despite this, at present, the goal in people with Head and Neck Cancer is not only focused on finding a cure. Due to this, an objective of great relevance is to enhance the quality of life of people, which shows a decrease by majority affection in three dimensions, among which the feeding and swallowing stand out. The clinical case report exposes the process of therapeutic intervention after radiotherapy in a 71-year-old patient. An intervention was performed that considered compensatory techniques in addition to myofunction rehabilitation exercises following the theoretical guidelines currently reported. Systematic adherence to the process has been an indispensable factor in the transition from exclusive initial feeding by gastrostomy to exclusive oral intake.
Keywords: Swallowing; Oropharyngeal dysphagia; Head and neck cancer; Myofunctional rehabilitation